2017
DOI: 10.1246/cl.170304
|View full text |Cite
|
Sign up to set email alerts
|

Highly Deliquescent Cationic Polyether with Imidazolium Halide Group

Abstract: A highly deliquescent cationic polyether was synthesized through living anionic polymerization of epichlorohydrin followed by quaternization of the obtained poly(epichlorohydrin) by reacting with 1-methylimidazole. The formed poly(N-glycidyl-N¤-methylimidazolium chloride) (poly(ECHMeIm + Cl ¹ )) absorbed moisture in air immediately to change its appearance from solid to fluid, suggesting its deliquescent nature. The hydrated poly(ECH-MeIm + Cl ¹ ) possessed neither glass transition nor phase transition in betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Polymerization of ECH. Polymerization of ECH was conducted using the following procedure, which is described in detail in the literature 38 and in the ESI. † The polymerization was carried out in a pre-baked ampoule tube equipped with a rubber septum at 0°C.…”
Section: Syntheses Of the Polymersmentioning
confidence: 99%
See 1 more Smart Citation
“…Polymerization of ECH. Polymerization of ECH was conducted using the following procedure, which is described in detail in the literature 38 and in the ESI. † The polymerization was carried out in a pre-baked ampoule tube equipped with a rubber septum at 0°C.…”
Section: Syntheses Of the Polymersmentioning
confidence: 99%
“…34 Recently, the quaternization of poly(ECH) with a well-controlled MW was studied by Baker et al 35,36 and by our group. 37,38 Baker's group focused on the synthesis and properties of cationic polyether with less polar butylimidazolium bis(trifluoromethanesulfonyl)imide in each repeating unit, however, the molecular structure has not been fully characterized. To our knowledge there is no report concerning cationized poly(ECH) with highly polar methylimidazolium chloride.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Hayano et al reported synthesis of polyether with imidazolium halide in the side chain by means of Menschutkin reaction of poly(epichlorohydrin) (PECH). 28,29 We came to an idea to synthesize the ionic gels from PECH.…”
mentioning
confidence: 99%